Enthralling Adsorption of Different Dye and Metal Contaminants from Aqueous Systems by Cobalt/Cobalt Oxide Nanocomposites Derived from Single‐Source Molecular Precursors. Issue 21 (1st June 2018) - Mohammad, Akbar; Ansari, Shagufi Naz; Chaudhary, Archana; Ahmad, Khursheed; Rajak, Richa; Tauqeer, Mohd.; Mobin, Shaikh M.
Abstract: The cobalt/cobalt oxide nanocomposites (Co/CoO NCs),  NC‐1  and NC‐2 were synthesizedfrom our recently reported single‐source molecular precursors (SSMPs) [Co(hep‐H)(H2 O)4 ]SO4, (1 ) and [Co(hep‐H)2 (H2 O)2 ](NO3 )2, (2 ), [hep‐H= 2‐(2‐hydroxylethyl) pyridine], respectively, via wet‐chemical reduction method. Our purpose was to study the effect of different counter anions (i. e. SO4 2− and NO3 − ) of precursors on the surface properties of synthesized materials. Both the nanocomposites were characterized by Powder X‐ray diffraction (PXRD), Scanning electron microscopy (SEM), Energy‐dispersive X‐ray analysis (EDAX), Transmission electron microscopy (TEM), Fourier transform infrared (FTIR) spectroscopy and Brunauer–Emmett–Teller (BET) analysis. Two distinct morphological as well as surface features have been obtained using1 and2 viz . variable spheres (NC‐1 ) with low surface area and flakes (NC‐2 ) with high surface area. The adsorption behavior of these nanocomposites on industrial dyes and metals showed excellent dye adsorption (99.6% to 97.2%) and good to moderate metal adsorption efficiency ofNC‐1 . TheNC‐1 could be recycled up to five times for dyes and three times for metals, advocating its practical applications in industry. Abstract : The cobalt/cobalt oxide nanocomposites (Co/CoO NCs),  NC‐1  and NC‐2 were synthesized from single‐source molecular precursors (SSMPs) using wet‐chemical reduction method. The adsorption of dyes (Congo Red, Chicago Sky Blue, Eosin B and Methyl Orange) and metals (Pb, Ce, Cr, Cu, Fe, Cd, As, Ni and Hg) on nanocomposite have been evaluated that suggested the practical applications in industry.